Ionization Rates of Electrons and Holes in GaAs Considering Electron-Electron and Hole-Hole Interactions - Singh S.R.; Pal B.B. (My University, 2025)
Calculations have been carried out for the ionization rates of electrons and holes in GaAs considering electron-electron and hole-hole interactions in addition to the optical phonon scattering, and the results have been compared with those of the experimentally observed values of both Ito et al. [1] and Pearsall et al. [2]. Fairly good agreement is found between the theoretical and experimental results. At the lower field region, the hole-ionization rate is larger than the electron-ionization rate and they meet at a field of the order of 108 V/m de-pending on the carrier concentration and other parameters; then, the hole-ionization rate becomes less than the electron-ionization rate. For the hole-ionization rate, at lower field range, holes behave as spin-orbit splitoff holes while at higher field they behave as heavy holes. The present study confirms that carrier-carrier interaction plays an important role in explaining the experimental results of ionization rates of carriers in GaAs and may be true for other semiconductors also. © 1985 IEEE